Noncontrast Hybrid Arterial Spin-Labeled Imaging of the Intracranial Arteries. Issue 6 (November 2017) - Lim, Ruth P.; Trajcevska, Elena; Al Rawi, Farah; Gooneratne, Dinesh; Ang, Windell; Perchyonok, Yuliya; Fitt, Gregory; Kemp, Andrew; Giri, Shivraman; Piccini, Davide; Brodtmann, Amy; Dewey, Helen; et al.
Abstract : Objective: The purpose of this study is to evaluate feasibility, image quality (IQ), and accuracy of noncontrast hybrid arterial spin labeling (NoHASL) magnetic resonance angiography (MRA) compared with time of flight (TOF) MRA and contrast-enhanced (CE) MRA in patients with known/suspected cerebrovascular ischemia. Methods: Thirty inpatients were imaged at 1.5 T. Two neuroradiologists assessed 630 intracranial arterial segments for IQ (1, nondiagnostic; 3, satisfactory for diagnosis; and 5, excellent). Hemodynamically significant stenosis (>50%) was assessed against all combined techniques as reference. Results: The NoHASL MRA IQ was diagnostic (3.32 ± 0.86) but affected by signal to noise ratio and spatial resolution limitations and significantly inferior to TOF (3.48 ± 0.68) and CE MRA (3.44 ± 0.78) ( P < 0.0001 in both comparisons). Fourteen (2.2%) of 630 segments had hemodynamically significant stenoses at the reference standard. Sensitivity/specificity was not significantly different between techniques: NoHASL MRA, 67.9%/90.0%; TOF MRA, 67.9%/97.7%; and CE MRA, 50.0%/98.7%. Conclusions: The NoHASL MRA is feasible, with diagnostic quality imaging of proximal intracranial vessels. Low disease prevalence limited the assessment of technique accuracy.